Evaluation of Butterfly Pea Flowers for Antioxidant Activity and its Potential as Antioxidant Soap - Abd Rashid, Nur Amira; Mohd Kassim, Anggzas Sari; Mohamed Rehan, 'Aisyah (Progress in Engineering Application and Technology, 2022)
Clitoria ternatea, often known as butterfly pea, is a flowering vine plant in the Fabaceae family with oval and acute leaves. Extraction is crucial to obtain its bioactive components which contribute to its antioxidant properties. Therefore, this study was performed to evaluate the antioxidant compounds found in C. ternatea extract obtained. DPPH assay was conducted in this study as a form of analysis of antioxidant compound in the Clitoria ternatea extract, with ascorbic acid used as the standard. The absorbance values were measured using UV-Vis spectrophotometer at 517nm. Though DPPH assay was fully performed, the results obtained from the assay did not fully match with other published studies. The discrepancy in the results may be due to the extraction method applied to obtain the butterfly pea flowers extract or the instability of the extract over time. Additionally, this study also conducted survey based on the potential antioxidant soap made from Clitoria ternatea extract. Once the soap was made and packaged, the soaps were distributed among 30 respondents and the respondents were asked to answer a questionnaire survey to study their preferences in soap and feedbacks after using this potential antioxidant soap from C. ternatea. In this survey, it is shown that after initial trial, respondents are most likely interested to use this butterfly pea flowers soap. A prospective study that follows the respondents using this soap over a period of time will be able to provide a significant data of its potential. Lastly, the estimation of cost analysis based on this soap shown that this soap has the potential of commercialized in the market as it can obtain high amount of profit per product sold.